Repetition of the Void Space Structure of Achimov Sandstones of the East Urengoyskoye Field in Artificially Created Geometry of a Silicon Microfluidic Chip - М. R. Latypova; D. I. Pereponov; V. V. Kazaku; А. Scerbacova; I. G. Maryasev; R. А. Mukhin; Е. D. Shilov; А. N. Cheremisin; V. L. Kosorukov; V. V. Churkina; М. А. Tarkhov; V. А. Shtinov; et al. (Georesursy, 2025)
In this work, a unique technique for replicating the void structure of a low-permeability reservoir in a silicon microfluidic chip has been developed. This technique is qualitatively superior to all previous ones and provides full repeatability of key parameters of the void structure (permeability; pore size distribution; average channel diameter; channel tortuosity, macro- to microporosity ratio) from digital core data. Moreover, the developed technique allows to exactly copy the pore geometry of the core sample from micro-CT images and recreate it inside the microfluidic chip. Using this technique, three artificial void space structures were developed for three samples of Achimov sandstones with different permeability (0.38; 2.04 and 9.86 mD). The mineralogical composition of the prototype samples was determined by a set of lithological and mineralogical studies and a positive correlation between the intensity of carbonate cementation and the decrease in permeability was revealed. Most of the macropores in the studied sandstones are associated with leaching of feldspars, and micropores are confined mainly to clay minerals. The conducted set of studies on the present samples will make it possible to extend the results of future filtration tests to rocks with similar mineralogical characteristics and filtration-capacitance properties. A qualitatively new method of creating inhomogeneous wettability of artificially created void space structure inside the microfluidic chip was developed. This technique consists in a smooth displacement of formation water from the microchip structure by a hydrophobic agent, which modifies wettability on the surface of macropores and channels, but does not enter the micropore structure due to residual water, which is held inside the microporous structures by capillary forces. Thus, this work is the first to apply a comprehensive multidisciplinary approach to replicate the core void structure within a microfluidic chip. In the future, this technique will be improved so that the results of filtration tests on microfluidic chips will even more reliably reflect fluid movement within the reservoir.